2002
DOI: 10.1080/00498250210158915
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of zaleplon by human liver: evidence for involvement of aldehyde oxidase

Abstract: 1. The metabolism of Zaleplon (CL-284,846; ZAL) has been studied in precision-cut human liver slices and liver cytosol preparations. 2. Human liver slices metabolized ZAL to a number of products including 5-oxo-ZAL (M2), N-desethyl-5-oxo-ZAL (M1) and N-desethyl-ZAL (DZAL), the latter metabolite being known to be formed by CYP3A forms. 3. Human liver cytosol preparations catalysed the metabolism of ZAL to M2. Kinetic analysis of three cytosol preparations revealed mean (+/- SEM) K(m) and V(max) of 93 +/- 18 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…The previously mentioned substrate zaleplon, a sedative drug used primarily for the treatment of insomnia, is a nonbenzodiazepine hypnotic that is cleared primarily by AOX (Lake et al, 2002). In addition, famciclovir, an antiviral prodrug used primarily to treat herpes virus infection is activated by AOX to its active 6-oxo form, penciclovir (Clarke et al, 1995;Rashidi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously mentioned substrate zaleplon, a sedative drug used primarily for the treatment of insomnia, is a nonbenzodiazepine hypnotic that is cleared primarily by AOX (Lake et al, 2002). In addition, famciclovir, an antiviral prodrug used primarily to treat herpes virus infection is activated by AOX to its active 6-oxo form, penciclovir (Clarke et al, 1995;Rashidi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…To date only one pharmacokinetic drug interaction due to the inhibition of AOX, between cimetidine and zaleplon, has been discovered (Lake et al, 2002). Predicting drug interactions with AOX is also relatively more difficult than with cytochrome P450 primarily because animal models are poor predictors of human AOX activity owing to the marked interspecies variation of expression levels and number of isoforms (Garattini and Terao, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A notable example is the recently introduced azaheterocyclic hypnotic agent, zaleplon (Kawashima et al, 1999;Lake et al, 2002), in which aldehyde oxidase generates the major metabolite 5-oxozaleplon as well as the corresponding 5-oxo analog of the N-dealkylated metabolite of zaleplon. Also, the bioactivation of famciclovir to the active antiviral agent penciclovir requires aldehyde oxidase-mediated metabolism (Clarke et al, 1995;Rashidi et al, 1997).…”
mentioning
confidence: 99%
“…The elimination of the tracer from the mouse body was attained via two routes; the first one is the kidneys through which the main radioactivity was eliminated (3.6%, 9.3%, 12.8%, and 4.6% at 5, 30, 60, and 120 minutes, respectively). The second route of tracer elimination was the liver, the total radioactivities detected in this excretory system were 2.8%, 6.1%, 7.3%, and 2.9% at 5, 30, 60, and 120 minutes, respectively) (Lake, Ball, Kao, Renwick, Price, & Scatina, 2002). In respect to the radioactivity taken up by the brain and that in the blood per gram tissues (target to non-target), it is concluded that the ratio increased with time passes and reached to its maximum value of 2.3 at 120 minutes post injection.…”
Section: Biodistributionmentioning
confidence: 99%